(untitled) (UNED Research Journal, 2018)
The rapid growth of motor vehicles use, together with poor waste disposal, produce environmental and biological threats. We evaluated the genotoxicity and enzyme activity of simulated automobile waste leachate in Swiss albino male mice (Mus musculus). Four mice per group were intraperitoneally treated with four leachate concentrations (10%, 15%, 20% and 25% v/v: simulant (IOASL)/distilled water), as well as a negative control (0.5mL UILSL); and a positive control (cyclophosphamide 20mg/Kg body weight) for five consecutive days. There was a concentration-dependent increase in sperm abnormality compared to the negative control (except at 10% and 15%; p<0,05). Heavy metal (Pb, Cd, As, Hg, Cr, Cu, Fe and Zn) exceeded permissible limits for waste water. Significant variability was also recorded in liver serum enzyme activity (AST, ALP, ALT and ALB) and in the frequencies of micronuclei (p<0,05). The interaction of some of these components with the genetic constitution of the cell during spermatogenesis might be responsible for the abnormalities.